Silicon kerf loss as a potential anode material for lithium-ion batteries - Søiland, Anne-Karin; de Meatza, Iratxe; Muguruza, Ane; Xu, Yijiang; Bellmann, Martin (Frontiers in Photonics, 2024)
In this work, industrially processed silicon kerf loss (abbreviated to silicon kerf) from the photovoltaic industry is assessed as an anode material for the lithium-ion battery (LIB). The study includes both a characterization of processed silicon kerf from different sources and a comparison with commercially available nano-sized silicon (40 and 100 nm) in electrochemical testing. Such a direct comparison between these two silicon types in electrochemical testing provides a new insight into silicon kerf as an anode material. The silicon kerf particles are flake-like with varying lengths, with a mean particle size (d50) measured to ∼700 nm and a dimension of thickness of a few tens of nanometers. However, the specific surface area ranging from 20 to 26 m2/g is comparable to that of a silicon material of size ∼100 nm. The silicon oxide layer surrounding the particles was measured to 1–2 nm in thickness and, therefore, is in a suitable range for the LIB. In terms of electrochemical performance, the silicon kerf is on par with the commercial nano-sized silicon, further supporting the size evaluation based on the specific surface area considerations. Initial discharge capacities in the range 700–750 mAh/g (close to the theoretical value for the 12 wt% Si mixture with graphite) and first cycle efficiencies of 86%–92% are obtained. The cycling stability is comparable between the two materials, although the differential voltage analysis (DVA) of the galvanostatic data reveals that only the silicon kerf samples maintain silicon activity beyond 120 cycles. This study shows that industrially processed silicon kerf has characteristics similar to nano-sized silicon without reducing the size of the silicon kerf particles themselves. Considering its low carbon footprint and potentially lower cost, it can thus be an attractive alternative to nano-sized silicon as an anode material for the LIB industry.